Dynamics of the operation of the peasant market of the Municipality of Suaza - Sánchez Castillo, Verenice; Lopez Ciceri, Cesar Julian; Thola Santofimio, Jime Esteban (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
The peasant markets in the municipality of Suaza (Huila) emerged as a method or alternative for the reactivation of the market place, it has also been a strategy to promote commercialization between the urban and rural sectors, being a practice implemented in several areas of Colombia. This study analyzes the dynamics of the operation of the peasant market in the Municipality of Suaza. For this purpose, the qualitative methodology with a hermeneutical approach was used, starting from the part of the historical-social paradigm through the use of the interview tool carried out with farmers, public officials and consumers. Among the results obtained, it is highlighted that the MC are the reason for important benefits for the peasant economy despite the low knowledge of marketing techniques and the different difficulties they face such as transportation to be able to bring their crops from the field to be well marketed in the urban sector. On the other hand, the great impact that it is generating in the Suazeña community because it is beginning to retake the market place, after 10 years of inactivity thanks to the implementation of peasant activities